TOKOH AGAMA DAN POLITIK: BIOGRAFI ABI LAMPISANG, 1962-2017 - Rizqal Fajri; Mawardi .; zulfan . (Universitas Syiah Kuala, 2018)
Abi Lampisang's figure is very interesting to study because of his prominent role and contribution in the field of religious and political education in Aceh As a religious figure Abi Lampisang has contributed to educating students and the community through the dayah he leads, while in the political arena Abi Lampisang has been heavily involved in various elections at both the district and provincial levels. The study, entitled